Sighted Students’ Perceptions about the Effectiveness of University Teachers with Visual Impairment: A Case Study - Ayesha Afzal, Shahid Rafiq (JIE, 2021)
The major premise of this research is to have an awareness of the perceptions of sighted students about the effectiveness of a teacher with visual impairment in one of the public universities of Lahore. Focusing on the actual pedagogical practices of a teacher with visual impairment in his/her teaching profession.